m-Health Based GERAT in Prevention and Early Detection of Pulmonary Tuberculosis in the Community of Tanjung Hilir Village Medan: GERAT Berbasis m-Health dalam Pencegahan dan Deteksi Dini Tuberkulosis Paru Pada Masyarakat Kelurahan Tanjung Hilir Medan - Yanti Silaban, Nataria; Lestari Simamora, Debora; Nugraha V. Naibaho, Eka; Devi, Devi; Putri, Putri (Universitas Haji Sumatera Utara, 2025)
Pulmonary tuberculosis is a bacterial infection caused by Mycobacterium tuberculosis and primarily affects lung tissue. The disease is transmitted through the air when an infected person coughs, sneezes, or talks, releasing germs into the environment. Symptoms of pulmonary TB can include a persistent cough, chest pain, fever, night sweats, and weight loss. If left untreated, pulmonary TB can be serious and potentially life-threatening. This health problem is closely related to the lack of public knowledge regarding early detection of pulmonary TB disease, resulting in a lack of awareness of the importance of early detection. Based on the results of field analysis obtained from the Medan Deli Health Center, where a very serious problem is the low public awareness of the importance of early detection of pulmonary TB and immediately checking the health center if they show signs and symptoms of the disease. This is also in accordance with data submitted by cadres during interviews where ten people were detected as having pulmonary TB and there were several people who had shown signs and symptoms such as coughing for 3 weeks or more and weight loss in the last 3 months, but did not want to go to the health center for examination on the grounds that it was just a normal cough and they were afraid. Objective: The form of activity packaged in this activity is the Anti-Tuberculosis Movement (GERAT) in the prevention and early detection of Pulmonary TB disease which is expected to be a breakthrough in improving health promotion in the community and become a sustainable and scheduled activity in cadre activities. Method The method used in this service is to use a quantitative method with a sampling technique of simple random sampling by conducting direct interviews and unplanned questions. The number of samples in this service activity is 50 people. The form of education that will be carried out by GERAT is packaged in interesting and interactive activities, using animated video media, booklets and posters and presented in offline and online forms with the mHealth (Mobile Health) application. The offline form carried out is a casual discussion with the community which begins with exploring community knowledge related to the concept of Pulmonary TB, prevention and early detection of Pulmonary TB disease, then continued with the presentation of counseling materials. Results. This community service activity has a sample of 50 people, where the community before the counseling the average knowledge value was 48.32% and after the counseling it became 89.78, which initially many people did not know how to prevent and detect Pulmonary TB early. Conclusion. With the Community Service activity, it can increase